Influence of E20 Fuelling on Combustion Cycle Variability at Turbocharged Spark Ignition Engine. (2016) - Obeid, Zuhair H.; Cernat, Alexandru; Pana, Constantin; Negurescu, Niculae; Nutu, Cristian
Abstract: The reduction of pollutant emissions from the automotive exhaust gases by using alternative fuels becomes a priority. The paper presents the preliminary results of cycle variability study for an aspirated spark ignition engine converted to turbo-supercharging and bioethanol fuelling for three areas of air-fuel ratio operating regimes, rich, stoichiometric and lean dosages. The influence of bioethanol content in blends with gasoline on cycle variability of the combustion process is reflected in the calculated values of the cycle variability coefficients. The cycle variability decreases at E20 use comparative to gasoline.